Values as a connecting bridge between religiosity and volunteering - Fényes, Hajnalka; Csák, Zsolt (Central European Journal of Educational Research, 2026)
Numerous studies examine behaviours associated with religiosity, including volunteering, which shows a positive correlation especially with collective religious practice. This effect may also derive from character development and value transfer associated with religiosity, based on certain studies. However, factors originating from religious community may be the primary drivers of this positive association. In our paper, we examine Schwartz’s four higher-order value dimensions as mediators between religiosity and volunteering. Using the European Social Survey 2023/24 database (N=42,489), we applied a mediation analysis in which individual-level effects of religiosity can be identified through indirect, value-mediated pathways, while effects originating from religious community can be identified through direct effects. Our results support the mediating role of values between religiosity and volunteering. However, the value-shaping effects of religiosity overall reduce the likelihood of volunteering, as religiosity primarily promotes conservation values, which in turn decrease the probability of volunteering. In contrast, our mediation model revealed a direct positive association between religiosity and volunteering. Based on our findings, religiosity contributes to higher volunteering behaviour primarily through the reinforcement of mutually supportive networks and prosocial norms, as well as through the provision of formal frameworks for volunteering in religious communities. Our future plans include incorporating more control variables into the model, which may nuance our results to date.